Sistem Pembuktian Gugatan Lain-Lain dalam Kepailitan - Yoshe Agatha Patricia (Jurist-Diction, 2022)
AbstractBankruptcy is a general confiscation of all debtor's assets to pay debtors' debts to all their creditors collectively. To file for bankruptcy, two requirements need to be met, namely the debtor has two or more creditors and debts that have matured and can be collected (Article 2 Paragraph (1) of the UUK and PKPU, if these two requirements have been fulfilled, the Commercial Court must grant the petition for bankruptcy based on Article 8 Paragraph (4) UUK and PKPU Consequences of general confiscation of the assets of a bankrupt debtor can cause new problems or disputes to the Commercial Court, but based on the explanation following the authority of Article 8 Paragraph (4) UUK and PKPU. So, in this case there is uncertainty about the procedure for examining other lawsuits based on the explanation of Article 3 Paragraph (1) of the UUK and PKPU against the bankruptcy authority as regulated in Article 8 Paragraph (4) UUK and PKPU. Keywords: Bankruptcy; Micellaneous Lawsuits; Debtors; Creditors; Commercial Courts. AbstrakKepailitan merupakan sita umum terhadap seluruh harta debitor untuk membayar utang-utang debitor kepada seluruh kreditor-nya secara kolektif. Untuk mengajukan permohonan pailit perlu dipenuhinya dua persyaratan yaitu debitor memiliki dua kreditor atau lebih dan utang yang telah jatuh tempo dan dapat ditagih (Pasal 2 Ayat (1) UUK dan PKPU, apabila telah terpenuhinya dua persyaratan tersebut maka Pengadilan Niaga harus mengabulkan permohonan pailit berdasarkan Pasal 8 Ayat (4) UUK dan PKPU. Konsekuensi dari sita umum terhadap harta debitor pailit, dapat menimbulkan permasalahan atau sengketa baru, berdasarkan Pasal 3 Ayat (1) UUK dan PKPU, permasalahan/sengketa yang timbul akibat kepailitan dapat diajukan sebagai Gugatan Lain-Lain ke Pengadilan Niaga, namun berdasarkan penjelasannya mengikuti kewenangan Pasal 8 Ayat (4) UUK dan PKPU. Sehingga dalam hal ini terdapatnya ketidakpastian tata cara pemeriksaan perkara Gugatan Lain-Lain berdasarkan penjelasan Pasal 3 Ayat (1) UUK dan PKPU terhadap kewenangan kepailitan sebagaimana diatur dalam Pasal 8 Ayat (4) UUK dan PKPU. Kata Kunci: Kepailitan; Gugatan Lain-Lain; Debitor; Kreditor; Pengadilan Niaga.